The Role of Travel Agency in Encouraging Sharia Tourism in Indonesia - Halmahera, Adityas; Bahri, Efri Syamsul (Journal of Multi-Disciplines Science, 2023)
Indonesia is a country with the largest population of Muslims in the world. It has the potential for an ordinary tourist attraction that has yet to become the primary choice of international Sharia tourists. With such a huge potential, Indonesia should be able to achieve its primary purpose. However, the condition of Indonesia has yet to be included in the top 10 destinations of world sharia tourism. On the contrary, Indonesian citizens become Sharia tourists with the purpose of other countries. One that plays a role in encouraging Indonesia to be the leading destination of Sharia tourism in Indonesia is the Travel Bureau. This study aims to determine the role of the Travel Agency in encouraging Sharia tourism in Indonesia. In addition, this research is meant to identify the factors that support and inhibit the role of the Travel Agency in encouraging Sharia tourism in Indonesia to become the world's leading tourist destination. This study's results indicate that no Travel Agency focuses on the Sharia tourism business in Indonesia. For that, the existence of the Travel Agency plays a significant role in encouraging Sharia tourism in Indonesia to be the primary goal.